Adaptive Backstepping Control of Single Chamber Microbial Fuel Cell. Issue 1 (2018) - Patel, Ravi; Deb, Dipankar
Abstract: This paper presents an adaptive backstepping control schemes applied to a single chamber microbial fuel cell (MFC) with single microorganism kinetics. The key advantage of the backstepping control scheme is its ability to handle systems with two or more relative degrees. We consider the control of the substrate concentration by using the dilution rate of the MFC system as a manipulated input variable. An adaptive action is provided for robustness against model uncertainties and online parameter estimation is performed. We have developed control algorithm using backstepping technique with adaptive action and have also provided Lyapunov stability analysis and ensured a convergent control scheme. The performance of the control schemes are illustrated using MATLAB/Simulink.